2007
DOI: 10.1111/j.1748-1716.2006.01645.x
|View full text |Cite
|
Sign up to set email alerts
|

Dantrolene, like fatigue, has a length‐dependent effect on submaximal force–length relationships of rat gastrocnemius muscle

Abstract: This study demonstrates that there is a length dependence of force depression associated with decreased Ca2+ release due to dantrolene treatment; therefore, if fatigue is due to decreased Ca2+ release, then additional length-dependent mechanisms are not required to explain the reported length dependence of force depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Thus, the force reduction due to the decrease of Ca 2+ release in fatigue conditions would be minimized when the muscle is demanded to contract at a bigger length than at a smaller one. This suggestion is supported by the findings by MacNaughton et al [27], who demonstrated a greater decrease of active force at a small muscle length in comparison with optimal muscle length. Moreover, at a bigger muscle length, less overlapping of actin and myosin is expected to occur than at a smaller muscle length [10].…”
Section: Discussionsupporting
confidence: 73%
“…Thus, the force reduction due to the decrease of Ca 2+ release in fatigue conditions would be minimized when the muscle is demanded to contract at a bigger length than at a smaller one. This suggestion is supported by the findings by MacNaughton et al [27], who demonstrated a greater decrease of active force at a small muscle length in comparison with optimal muscle length. Moreover, at a bigger muscle length, less overlapping of actin and myosin is expected to occur than at a smaller muscle length [10].…”
Section: Discussionsupporting
confidence: 73%
“…In some cases, Ptw was estimated from the first bump of the incompletely fused tetanic contraction at 50 H Z . This frequency of stimulation is commonly used to elicit fatigue in mammalian muscles 21, 26…”
Section: Methodsmentioning
confidence: 99%
“…This frequency of stimulation is commonly used to elicit fatigue in mammalian muscles. 21,26 Experiment 1. In the first experiment, the consequences of intermittent repetitive stimulation on summation were evaluated (n ¼ 8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, comparisons between changes in summation during fatigue and recovery with corresponding changes in the presence of dantrolene, a drug that inhibits Ca 2+ release through RyR,17, 18 may be informative. Dantrolene has been used successfully in studies comparing contractile changes with Ca 2+ inhibition and those associated with low‐frequency fatigue,19–21 but not in association with summation.…”
mentioning
confidence: 99%